Transformed radial stub cell embedded resonator for high performance filter applications - Ma, Kaixue (2013)
Parasitic passbands of the traditional resonators or bandpass filters are drawbacks for the resonator or filter to achieve wide stopband. A bandpass filter topology designed based on the embedded transformed radial stub cells is proposed for the first time. The implemented filter with center frequency ƒc=1.73 GHz and absolute bandwidth of 200MHz (fractional bandwidth of 1.2%) using transformed radial stub cell embedding demonstrates more than 45dB rejection up to 10.4ƒc i.e. 18 GHz. The measured group delay is around 3.6∼4.3 nS. The sizes of the designed fourth order bandpass filter is only 0.42 λg × 0.26 λg, (λg is the guide wavelength at center cutoff frequency) without using any lumped elements.